Attitudes and motivations following shortened 2020 season among NCAA Division II und Division III baseball players: a pilot study - Andrew, S. C.; Brandon, W.; David, M.; Warner, L.; Diana, G.; Laurel, T.; Christina, T.; Julie, G. (Research & Investigations in Sports Medicine, 2020)
In response to the global spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the National Collegiate Athletic Association (NCAA) cancelled all 2020 winter and spring championships that had not been completed. As a result of this cancellation and increasing travel restrictions, many conferences and institutions elected to cancel the remainder of their regular seasons for the 2019-2020 academic year. In response to these cancellations, the NCAA voted in favor of granting student-athletes who participated in spring sports and met certain criteria an extra year of eligibility. Currently, research is being conducted to evaluate the epidemiology, recognition, treatment and prevention of coronavirus disease 2019 (COVID-19), the disease associated with SARS-CoV-2. However, there does not appear to be any published research on the attitudes and motivations of NCAA spring sport student-athletes following the cancellations of their seasons and subsequent issuance of an extra year of eligibility. Therefore, the purpose of this pilot study is to describe the attitudes and motivations of collegiate baseball players at an NCAA Division II and NCAA Division III institution. A total of 47 collegiate baseball players participated in this study (Division II = 28; Division III = 19). Participants were sent an electronic survey via email that collected demographic information and assessed attitudes and motivations regarding the shortened season and extra year of eligibility. Data was downloaded and analyzed using a commercially available statistics package (SPSS Version 26, IBM, Armonk, NY). The overwhelming majority of collegiate baseball players surveyed in this pilot studied were disappointed and/or angry about the 2020 season being shortened (Disappointed = 100%; Angry = 61.7%). Of the baseball players who were going to be out of eligibility before the NCAA decision, 33.33% (n=7) stated they intended to make use of their additional year of participation. Additionally, the majority of baseball players reported they were more excited about next season as a result of this season being shortened (74.47%, n=35). Between the two groups, there were not significant differences with regards to attitudes toward the shortened season. However, more Division III baseball players cited graduation and job offers as reasons they would not be using their additional year of eligibility. This pilot study serves as validation for a larger scale study on multiple NCAA baseball teams to determine the overarching attitudes and motivations following the shortened 2020 season.